(untitled) (Research, Society and Development, 2020)
The article aims to objective was to map the production of scientific research from the search for studies that deal with Early Childhood Education in the last quadrennium of Capes (2013-2016). 151 articles were analyzed, aiming at constituting an overview of the production and locating the type of establishment (kindergarten/pre-school) in which the researches were carried out, the methodologies and keywords that have a greater presence in the constitution of these productions. Based on a qualitative and quantitative study, we used the systematic review procedures based on the analysis of Qualis journals with stratum A1 to B2. The results indicate that, in general, the research analyzed on early childhood education privileges institutions that attend kindergarten and pre-school simultaneously, adopting as methodology the documentary or bibliographic analysis with a qualitative approach with a predominance of studies dealing with "public policies". It is concluded that the production of knowledge in Early Childhood Education has been growing, which makes it a sub-area of Education that interfaces with several others, and that requires the need for attention, since the production of knowledge from Postgraduate Studies should not be only to meet the evaluation criteria imposed by Capes, but to actually contribute to the advancement of the area in question.